Udang Sarap (Caridina sp) Abundance in Tanjung Putus, Indralaya, South Sumatra - Marisa, Hanifa (Jurnal Penelitian Sains, 2024)
Investigations have been carried out on the abundance of sarap shrimp, Caridina sp in the waters along the Kelekar river, Indralaya at the end of February 2023. Three sampling locations were chosen, namely 200 m north of the Tanjung Senai bridge, 100 m north of the bridge (the mouth of the Unsri reservoir outlet) and just under the Tanjung Senai bridge . Sampling was carried out using fishing gear made from coconut milk filter with a diameter of 20 cm with a 1 m stem and each location was repeated 10 times, with  filtered water volume is 15 liters. Recording was carried out on the average of prawns caught, habitat vegetation species and general water conditions. The result was that upstream, 200 m from the bridge, 2.6 individuals/liter were found with calm water conditions and vegetation of Salvinia sp, Utricularia sp, and Leersea sp. At a distance of 100 m upstream, the vegetation was the same, but no shrimp were caught, except for one the little snakehead fish was still red. The water here is the confluence of the embung outlet and the Kelekar river. The location is under the bridge, the edge of the water is calm, the vegetation is the same but 10 individuals/liter were found. It was concluded that the riverside waters are calm and overgrown with aquatic vegetation, suitable for Caridina sp to live except at the confluence of rivers and outlets where there is more current and there are predators such as snakehead fish.